Use of preprocurement biopsy in donation after circulatory death liver transplantation. Issue 11 (12th June 2022) - Bolognese, Alexandra C.; Foley, David P.; Sparks, Carrie J.; Schneider, Adam K.; D'Alessandro, Anthony M.; Neidlinger, Nikole A.
Abstract: We perform routine preprocurement image‐guided percutaneous liver biopsies on potential donation after circulatory death (DCD) liver donors. The purpose of this study was to examine the impact of preprocurement liver biopsy on the use of livers from DCD donors. We retrospectively reviewed demographics, liver histology, and disposition of DCD liver donors within a single organ procurement organization (OPO) who underwent preprocurement liver biopsy from January 2000 through December 2019. A total of 212 potential donors underwent prerecovery biopsy. No donors were lost as a result of complications of biopsy. Of these, 183 (86.3%) had acceptable biopsies: 146 (79.8%) were successfully transplanted and 37 (20.2%) were deemed not suitable for transplant. In contrast, of 120 DCD livers recovered with the intent to transplant that were not biopsied prior to recovery, 59 (49.2%) were successfully transplanted, and 61 (50.8%) were deemed not suitable for transplant. A total of 14 donors were ruled out for transplant based on prerecovery histology. Successfully transplanted livers that underwent preprocurement biopsy were more likely to come from donors aged older than 50 years or with body mass index more than 30 kg/m 2 compared with successfully transplanted livers without a prerecovery biopsy. Biopsy excluded 6.6% of DCD donor livers for transplant prior to recovery and facilitated the successful recovery and transplant of two‐thirds of potential DCD donor livers. Livers intended for transplant at the time of recovery that did not undergo preprocurement biopsy were more likely to not be recovered or to be discarded. Preprocurement biopsy provides additional histologic information prior to deploying resources and helps to identify usable livers that might otherwise be declined for transplant. Consideration of liver biopsy in this group benefits OPOs and transplant centers by maximizing organ use and optimizing resource deployment.